Impact of fibre factor and temperature on the mechanical properties of blended fibre-reinforced cementitious composite - Liang Liu (Elsevier, 2022)
Blended fibres are being utilized in ordinary Portland cement-based materials (CBMs). The inclusion of blended fibre (a mix of several fibre types) may help CBMs perform better under fire. Fibre factor (F.F) and mechanical characteristics of blended fibre-reinforced CBMs are investigated in this research under various temperature conditions. In addition to mechanical characteristics, empirical models for strength properties in response to temperature and F.F. are established. The addition of calcite powder to blended fibres in CBMs increased mechanical strength across the board at all temperatures. However, increasing the temperature from 20 °C to 750 °C resulted in 75%, 79%, and 84% reductions in compression, split tension, and flexure strength of blended fibre-reinforced CBMs, respectively. For compression, split tension, and flexure strength, empirical models with R2 values of 0.98, 0.92, and 0.93 were constructed, with fibre factor and temperature as the major affecting variables. Experimental data for blended fibre-reinforced CBMs revealed that empirical models predicted superior outcomes, which was brought into existence.